Inequality in an OLG Economy with Heterogeneous Cohorts and Pension Systems - Joanna Tyrowicz; Krzysztof Makarski; Marcin Bielecki (Institute of Labor Economics (IZA), 2018)
We analyze the consumption and wealth inequality in an OLG model with mandatory pension systems. Our framework features within cohort heterogeneity of endowments and heterogeneity of preferences. We allow for population aging and gradual decline in TFP growth. We show four main results. First, increasing longevity translates to substantial increases in aggregate consumption inequality and wealth inequality. Second, a pension system reform from a defined benefit to a defined contribution works to reinforce consumption inequality and reduce wealth inequality. Third, minimum pension benefits are able to partially counteract an increase in inequality introduced by the defined contribution system, at a fiscal cost. Fourth the minimum pension benefit guarantee mostly addresses the sources of inequality which stem from differentiated endowments rather than those which stem from heterogeneous preferences.
Keywords: H55; E17; C60; C68; E21; D63; 330; consumption; wealth; inequality; longevity; defined contribution; defined benefit